Clinicobacteriological and Radiological Profile of First Episode of Urinary Tract Infection In Patients In The Age Group From 1 Month To 14 Years In A Tertiary Care Hospital,A Prospective Observational Study - Kodam Mahidhar, Mrutunjay Dash, Antaryami Pradhan (International Journal of Advanced Science and Technology, 2020)
Urinary Tract Infections (UTI)  is one of the most common bacterial infections in children presenting often as a case of fever of unknown origin. Around 50% of the cases are missed, probably due to its varied and nonspecific symptoms. Therefore the knowledge of the bacteriological profile of the community and the importance of radiological work up is essential. To study the clinical features, radiological abnormalities and bacteriological profile of children presenting with first episode of UTI. All children aged 1 month to 14 years admitted with symptoms suggestive of UTI in pediatric ward of IMS & SUM HOSPITAL, BHUBANESWAR from August 2017 to August 2019 were enrolled for the study. The statistical analysis was done using SPSS version. Out of 80 children admitted with UTI, 65% were boys and 35% were girls with male to female ratio being 1.8:1.Maximum cases were seen between the age group of 1month - 5years.Fever(91%) was the most common presenting symptom, followed by vomiting(51%),lower abdominal pain(45%) and burning micturition (41%).The most common uropathogen isolated was Eschericia coli(73.5%), followed by Klebsiella pneumonia (12.5%) and Proteus mirabilis (7.5%). Cystitis (10%) was found to be the most common ultrasonographic finding, followed by upper urinary tract dilatation in 7.5%. Among 80 patients 4 were found to have complications i.e. Acute kidney Injury and Septicemia. CONCLUSION :Overall, males had a higher prevalence of UTI in the current study, May be attributed to more number of parents seeking medical attention of boys. Although there can be a variable clinical spectrum, but fever and vomiting were the commonest presentations in UTI in children. E. coli is the most widely prevalent organism causing UTI in children. Ultrasonography is advised in all the patients diagnosed with UTI. It is a sensitive test in detecting abnormality in renal parenchyma and urinary tract abnormalities. A hospital specific antibiotic policy should be established for UTI and good scrutiny measures should be taken to ensure the effectiveness of the same.